2019
DOI: 10.1111/jfpp.14178
|View full text |Cite
|
Sign up to set email alerts
|

The effect of microwave and convective dryer with ultrasound pre‐treatment on drying and quality properties of walnut kernel

Abstract: In this study, the drying kinetics of walnuts was investigated including specific energy consumption (SEC), shrinkage, and walnut kernels' color in two dryers, namely ultrasonic‐convection (US‐CON) and ultrasonic‐microwave (US‐MIC). To carry out this study, walnut samples were dried at three MIC powers (270, 450, and 630 W), three input air temperatures (40, 55, and 70°C) and four duration of ultrasonic pre‐treatment (0 min (control sample), 10, 20, and 40 min). Fifteen mathematical models were used to describ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
57
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 69 publications
(68 citation statements)
references
References 79 publications
(119 reference statements)
11
57
0
Order By: Relevance
“…As a result, product shape changes and occasionally leads to cracking of the product (Onwude et al, ; Zhang et al, ). Similar reports have been published for pumpkin fruit (Junqueira et al, ), hawthorn (Amiri Chayjan, Kaveh, & Khayati, ), walnut kernel (Abbaspour‐Gilandeh, Kaveh, & Jahanbakhshi, ) and walnut (Jafarifar, Chayjan, Dibagar, & Alaei, ).…”
Section: Resultssupporting
confidence: 83%
“…As a result, product shape changes and occasionally leads to cracking of the product (Onwude et al, ; Zhang et al, ). Similar reports have been published for pumpkin fruit (Junqueira et al, ), hawthorn (Amiri Chayjan, Kaveh, & Khayati, ), walnut kernel (Abbaspour‐Gilandeh, Kaveh, & Jahanbakhshi, ) and walnut (Jafarifar, Chayjan, Dibagar, & Alaei, ).…”
Section: Resultssupporting
confidence: 83%
“…These networks have high accuracy and take a little time to obtain results. Abbaspour‐Gilandeh et al, (2019) suggested the 3‐12‐12‐1 topologies with (R2 = .9993) of ANNs to evaluate the quince MR under the convective dryer. Ozdemir, Aktaş, Şevik, and Khanlari (2017) applied the ANNs to predict the italicMR of kiwifruit with (R2 = .998) in a convective‐infrared dryer.…”
Section: Resultsmentioning
confidence: 99%
“…The MC percentage of the pistachio kernel was measured by weighing them by a digital scale every 5 min until they reached a fixed weight of 10 ± 0.05% (d.b.) (Abbaspour‐Gilandeh, Kaveh, & Jahanbakhshi, 2019). At least three replicates of the experiment were made .…”
Section: Methodsmentioning
confidence: 99%
“…Among these methods, microwave drying has attracted significant attention from researchers because of its high drying velocity, relatively low energy consumption and its ability to preserve the good nutrients. Microwave drying has been successfully applied to agricultural, forestry and food products, such as oil crops, ginkgo fruit, grain, tea, mushroom, and chili peppers, among other products (Abbaspour-Gilandeh, Kaveh, & Jahanbakhshi, 2019;Amer et al, 2019;Nathakaranakule, Paengkanya, & Soponronnarit, 2019).…”
mentioning
confidence: 99%